Investigation of aerodynamics and longitudinal stability of unmanned aerial vehicle with elevator deflection - Ngoc, Hoang Thi Bich; Binh, Bui Vinh (Vietnam Journal of Mechanics, 2019)
The elevator is usually hinged to the horizontal tail, which acts as a balance and controls the altitude, establishes a steady motion for the aircraft at all lift coefficients. During elevator rotating, the aircraft needs to be stable to establish a new altitude. The horizontal tail has a major role in the value of the airplane’s pitching moment (due to the long arm from the aerodynamic center of the tail to the center of gravity) for the equilibrium and stability of the aircraft. The horizontal tail should be considered as an aerodynamic component behind the main wing, influenced by the wing downwash wing rather than just a minor wing. Therefore, the aim of this study is to examine the flow through unmanned aerial vehicles (UAV) including the main wing, tail and body and to calculate the aerodynamic force on the horizontal tail when rotating the elevator using the Fluent software for the viscous flows. Small disturbance theory was used to calculate the longitudinal stability of the UAV when controlling the elevator. Flying qualities are assessed to show that changes in the aerodynamic characteristics of the wing, tail, fuselage and configuration of the UAV may be required.